Strongly aligned coastal boulders on Ko Larn island (Thailand): a proxy for past typhoon‐driven high‐energy wave events in the Bay of Bangkok. (10th May 2019) - Terry, James P.; Goff, James
Abstract: Recent studies of elevated carbonate boulder deposits on several rock islands near Bangkok have indicated that Thailand's capital city may not be as protected from typhoon strikes as previously thought. Here, new evidence is presented for past high‐energy wave (HEW) events in the form of statistically significant patterns of boulder alignment on exposed rocky shorelines of Ko Larn island. The long‐axis orientations of 193 coastal sandstone boulders were analysed across four study sites. Several scenarios for the unimodal, bimodal, and polymodal patterns found can be envisaged. Either the most recent HEW event was the strongest—in which case most clasts were rearranged unimodally (one observation site), or the strongest HEW event was earlier and subsequent weaker ones realigned only smaller boulders to produce bimodal or polymodal patterns (three observation sites). Inferred northeastward or eastward onshore flow directions are consistent with palaeo‐typhoons penetrating into the Bay of Bangkok on northwestward curving tracks. The calculated minimum flow velocities required to transport all sampled boulders are 5.5–7.8 m s −1, similar to other findings throughout the Asia‐Pacific region. It was observed that the absence of a fitted boulder geomorphology lends credence to the earlier proposed time frame of 150–200 years between typhoon phases in the upper Gulf of Thailand. The current work has provided additional insights into the characteristics of past HEW events that have a possibility of reoccurring again at some time in the future. Our findings continue to raise awareness for a reassessment of the risks of coastal hazards for the Chao Phraya River delta and densely populated Bangkok, for which storm surge modelling should be an urgent priority, so as to give better perceptions on how typhoon‐driven marine incursion would impact the city.